“Board independence” and compensation structure of directors - Merino, Elena; Manzaneque, Montserrat; Priego, Alba Maria (Copernican Journal of Finance & Accounting, 2013)
This paper examines the relationship between board independence and the level and structure of directors´ compensation to determine whether this “independence” exerts a moderating effect on the different systems of remuneration granted to directors. We have developed several models based on linear panel data regression. The sample included 76 listed companies on the Spanish Continuous Market for the period 2004–2009. The results reveal that the moderating effect of board independence on directors´ compensation depends on the type of remuneration, being especially significant in the case of variable remuneration but not for fixed remuneration. This is significant for the study context because the fixed remuneration is the most important retribution concept. The results of this paper reveals that the inefficient of the board as mechanisms of control on fixed remuneration could be translated into an insufficient control of wealth extraction from the shareholders by the management. Our results contribute to the existing debate on the appropriate norms of corporate governance control over the directors’ compensation. These results offer additional evidence about the impact of board independence over the structure of compensation granted to directors, issue shortly studied so far.